Review of Scott McMillin and Sally-Beth MacLean, 'The Queen's Men and their plays' (Cambridge: Cambridge University Press, 1998) - Gabriel Egan (1999)
Review of Scott McMillin and Sally-Beth MacLean, 'The Queen's Men and their plays' (Cambridge: Cambridge University Press, 1998)